Differences in atrial fibrillation management strategies among physicians: A survey based study - Sara Cetin Sanlialp; Ugur Onsel Turk; Kaan Okyay; Ozcan Basaran; Ugur Canpolat; Mehdi Zoghi (International Journal of the Cardiovascular Academy, 2019)
Aim: Previous data reflected confusions about classification and management of atrial fibrillation (AF) among physicians. Although relatively clear suggestions of dedicated guidelines, poor adaptation of them to routine clinical practice may result with suboptimal prevention and treatment measures. As a main stakeholder of management, physicians' perceptions about the disease have major role. The study aimed to assess confusions and concordances of physicians about the definition and management of the disease. Methods and Results: We developed a web-based survey about AF consisting of 27 questions regarding valvular or non-valvular AF perception, using thromboembolic and bleeding risk scores, antithrombotic management and rate/rhythm control strategies. Two hundred and thirty two physicians participated and 224(97%) of them completed the survey. Although only cardiologists were invited to the survey, 27 physicians from different specialties also responded the survey. Half of the physicians reported that ≥40% of their patients had valvular AF. Dramatically, the survey responses revealed that nearly one-third of physicians classified the AF patients with mitral regurgitation as valvular AF. Most of the physicians denoted that they were using bleeding and stroke risk scores before deciding oral anticoagulation therapy and also preferring long term rhythm-control strategy in AF patients with systolic heart failure. However, results exposed evident disparities among physicians at specific aspects of the disease management. Conclusion: The survey-based study demonstrated a great heterogeneity in classification and management of AF among physicians because of guideline confusions/failures, inadequate evidence about some specific conditions and not being able to dominate the guidelines by physicians.